Ilusión y materialidad : perspectivas sobre el archivo - Pizarro, Jerónimo; Guzmán Méndez, Diana Paola (Ediciones Uniandes : Universidad de los Andes, Facultad de Artes y Humanidades, Departamento de Humanidades y Literatura, 2018)
This book is the result of a series of open forums in which the conservation, conformation, circulation and appropriation of the bibliographic collections in general was discussed, and very particularly of some literary archives of the nineteenth and twentieth centuries.